Kemampuan Literasi Matematis Siswa SMK dalam Menyelesaikan Soal Geometri - Nabila, Intan; Aminah, Mimih (JRPM (Jurnal Review Pembelajaran Matematika), 2025)
This study aims to examine the mathematical literacy ability of Grade XI vocational school students in Sumedang Regency in solving geometry problems. The research employed a descriptive qualitative approach, with data collected through written tests, interviews, and documentation. The findings revealed that the average mathematical literacy ability of students was classified as adequate, with 65% of students falling into this category. The highest indicator of mathematical literacy ability was recognizing mathematical components in real-life problems (70%), while the lowest was evaluating and interpreting mathematical results (30%). Students faced challenges in solving geometry problems, such as errors in using formulas, ineffective problem-solving strategies, and a lack of interpretation of results. These difficulties highlight the importance of integrating real-life context-based problems into learning to enhance students' mathematical literacy ability. Such an approach helps students better understand and apply mathematical concepts meaningfully. This study emphasizes the need to address these challenges by designing targeted instructional methods. By incorporating practical examples and offering comprehensive support, educators can help students overcome their weaknesses. The findings are expected to serve as a foundation for developing effective teaching methods aimed at improving students’ mathematical literacy, enabling them to apply mathematics confidently in real-world contexts.